2022
DOI: 10.1017/s2045796022000427
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of quality of life in young people attending primary mental health services

Abstract: Aims The utility of quality of life (QoL) as an outcome measure in youth-specific primary mental health care settings has yet to be determined. We aimed to determine: (i) whether heterogeneity on individual items of a QoL measure could be used to identify distinct groups of help-seeking young people; and (ii) the validity of these groups based on having clinically meaningful differences in demographic and clinical characteristics. Methods Young people, at their first presentation to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…php/aqolinstruments?id=92), using Australian population preference weights. The distribution of AQoL-6D instrument item specific scores within our sample has been described in a previous study [17].…”
Section: Methodsmentioning
confidence: 99%
“…php/aqolinstruments?id=92), using Australian population preference weights. The distribution of AQoL-6D instrument item specific scores within our sample has been described in a previous study [17].…”
Section: Methodsmentioning
confidence: 99%
“…Via latent class analysis (LCA), we differentiated by demographic and clinical features four subgroups of young people based on their responses to items on the Assessment of Quality of Life – 6 dimensions (AQoL-6D) scale. 28 We concluded that including multi-attribute utility instruments such as the AQoL-6D to routine data collection in mental health services might generate insights into the care needs of specific subgroups of young people beyond reducing psychological distress and promoting symptom recovery. 28 Another study identified young people vulnerable to social exclusion across domains of housing, work and study, social functioning, and lifestyle factors.…”
Section: Understanding the Heterogeneity And Complexity Of Mental Hea...mentioning
confidence: 98%
“…28 We concluded that including multi-attribute utility instruments such as the AQoL-6D to routine data collection in mental health services might generate insights into the care needs of specific subgroups of young people beyond reducing psychological distress and promoting symptom recovery. 28 Another study identified young people vulnerable to social exclusion across domains of housing, work and study, social functioning, and lifestyle factors. 29 Those experiencing multiple domain vulnerabilities reported greater mental health needs; for example, those not in education, employment and/or training (NEET) and with unstable housing had higher levels of distress, substance use, poor functioning, and lower social support.…”
Section: Understanding the Heterogeneity And Complexity Of Mental Hea...mentioning
confidence: 98%
“…To demonstrate the need for ensemble clustering in psychology, we conducted simulations using datasets from three published studies (Amiet et al, 2020;Cotton et al, 2022;Jakobson & Rigby, 2021) (see details of these studies in Table S3 in Supplementary Material I). The primary aim of these simulations was to assess the stability of different clustering algorithms with perturbation introduced into the data.…”
Section: Comparisonmentioning
confidence: 99%